How Does Regular Cow's Milk Consumption Combined With Vitamin D Supplementation Affect Nutritional Status And Growth In Malnourished Children ? : A Systematic Review - Putu Ratna Rosalina; Salmawati Maryati (The International Journal of Medical Science and Health Research, 2025)
Introduction: Malnutrition in children, particularly in low- and middle-income countries, remains a significant global health issue, impairing physical growth and cognitive development. Cow's milk, rich in essential nutrients, and Vitamin D, crucial for bone health and immune function, are vital for child development. This systematic review evaluates the impact of regular cow's milk consumption combined with Vitamin D supplementation on the nutritional status and growth of malnourished children. Methods: This systematic review adhered to PRISMA 2020 guidelines. Studies were screened based on criteria including: children aged 6 months to 12 years meeting WHO malnutrition criteria; intervention with regular cow's milk (minimum 200ml/day) and Vitamin D supplementation; study duration of 3 months or longer; and study designs such as RCTs, systematic reviews, meta-analyses, or prospective cohort studies. Data were extracted from databases including Pubmed, Semantic Scholar, Sagepub, and Google Scholar. Results: The review included 27 studies. Findings indicated that fortified cow's milk with Vitamin D supplementation generally improved Vitamin D status. For instance, some studies showed serum 25-hydroxyvitamin D levels increased by approximately 20 ng/mL with supplementation. Effects on growth metrics like height and weight were modest and variable, with some studies reporting significant improvements (e.g., height-for-age z-scores, p < 0.0001 ) while others found no significant effect. Interventions combining milk with other nutrient sources like eggs or micronutrient powders showed more pronounced effects on growth (e.g., a 2.62 cm increase in height ). Longer intervention durations (≥6 months) and higher doses (e.g., 600 ml milk daily) were often associated with better outcomes for micronutrient status and growth. Discussion: The evidence suggests that fortified cow's milk and Vitamin D supplementation effectively enhances micronutrient status, particularly Vitamin D levels, in malnourished children. While the direct impact on linear growth and weight gain is modest, comprehensive intervention packages addressing multiple deficiencies simultaneously appear most effective. The variability in growth outcomes underscores the importance of considering baseline nutritional status, intervention duration, and dosage. Conclusion: Fortified cow's milk and Vitamin D supplementation is a valuable strategy for improving micronutrient status in malnourished children, especially Vitamin D levels. Although growth improvements can be modest, integrating this intervention into broader, holistic nutritional programs, particularly with longer durations and adequate dosages, is supported by evidence and crucial for mitigating malnutrition.